Computational fluid dynamic and corrosion study on discharge of pyrotechnic condensed fire suppression aerosol - Hee, Choi; Ismail, Mohd Halim Shah; Ahmadun, Fakhrul-Razi; Mohamed Yusoff, Hamdan (IDOSI Publications, 2015)
Condensed aerosol fire extinguishing technology is relatively a new fire suppression technology in fire extinguishing research and industry. In current market, almost all condensed aerosol forming agents contain potassium nitrate or perchlorate as an oxidant which generates corrosive potassium oxides and salts after agent combustion. In this research, copper metal plate is found to be very vulnerable to corrosions caused by potassium compounds and contents of potassium based oxidants and corrosion potentials of four commercialized aerosol forming agents were analyzed. The four aerosol forming agents have similar contents of potassium based oxidants and their corrosion potential after combustion and discharge should be close to each other. Besides corrosion study of different K-type aerosol on metal plates, Computer Fluid Dynamic (CFD) modeling of aerosol motion during and after discharging in a large confined room was carried out. Higher aerosol discharging velocity and specifically directional arrangement of canisters help the distribution of aerosol momentum, which is beneficial to the increase of fire extinguishing efficiency and fewer aerosol forming agents are needed if fire extinguishing efficiency per agent is elevated. Fires which are shed or covered by objects in a compartment are hard to be extinguished and aerosol of high momentum is required for extinguishing fires under covers. It is the first time that computer fluid dynamics modeling was applied for pyrotechnic aerosol fire extinguishing study. Reynolds Averaged Navier Strokes equations and discrete finite volume method was used for treating the turbulent aerosol and fire.